Dengue virus‐infected human dendritic cells reveal hierarchies of naturally expressed novel NS3 CD8 T cell epitopes. (September 2014) - Piazza, P.; Campbell, D.; Marques, E.; Hildebrand, W. H.; Buchli, R.; Mailliard, R.; Rinaldo, C. R.
Summary Detailed knowledge of dengue virus (DENV) cell‐mediated immunity is limited. In this study we characterize CD8+ T lymphocytes recognizing three novel and two known non‐structural protein 3 peptide epitopes in DENV‐infected dendritic cells. Three epitopes displayed high conservation (75–100%), compared to the others (0–50%). A hierarchy ranking based on magnitude and polyfunctionality of the antigen‐specific response showed that dominant epitopes were both highly conserved and cross‐reactive against multiple DENV serotypes. These results are relevant to DENV pathogenesis and vaccine design.